The role of two branched‐chain amino acid transporters in Staphylococcus aureus growth, membrane fatty acid composition and virulence. Issue 5 (27th September 2016) - Kaiser, Julienne C.; Sen, Suranjana; Sinha, Anshul; Wilkinson, Brian J.; Heinrichs, David E.
Summary: The branched‐chain amino acids (BCAAs) are vital to both growth and virulence of the human pathogen Staphylococcus aureus . In addition to supporting protein synthesis, the BCAAs serve as precursors for branched‐chain fatty acids (BCFAs), which are predominant membrane fatty acids, and, in association with the global regulatory protein CodY, the BCAAs are key co‐regulators of virulence factors. Despite these critical functions, S. aureus represses Leu and Val synthesis, instead preferring to acquire them from the extracellular milieu. We previously identified BrnQ1 as a BCAA transporter, yet a brnQ1 mutant remained capable of BCAA acquisition. Here, we describe BcaP as an additional BCAA transporter, and determine that it plays a secondary role to BrnQ1 during S. aureus growth in a chemically defined medium. Furthermore, membrane fatty acid composition analysis revealed that BrnQ1, and not BcaP, is required for transporting Leu and Val to be used for iso‐BCFA synthesis. Despite a predominant role for BrnQ1 in vitro, both BrnQ1 and BcaP are required for S. aureus fitness in vivo in a hematogenous spread infection model and a nasal colonisation model. These data demonstrate the importance of BrnQ1 and BcaP for growth, environmental adaptation and virulence of S. aureus . Abstract : The branched‐chain amino acids (BCAAs; Ile, Leu, Val) are important nutrients for Staphylococcus aureus physiology and virulence, and yet it does not readily synthesize Leu and Val. Here, we show that S. aureus acquires free BCAAs via the transporters BrnQ1 and BcaP. Although BrnQ1 plays a predominant role in supplying Leu and Val for growth and synthesis of branched‐chain fatty acids in vitro, both BrnQ1 and BcaP are required for optimal fitness of S. aureus in vivo .